2020
DOI: 10.1158/0008-5472.can-20-0624
|View full text |Cite
|
Sign up to set email alerts
|

Cancers from Novel Pole-Mutant Mouse Models Provide Insights into Polymerase-Mediated Hypermutagenesis and Immune Checkpoint Blockade

Abstract: POLE mutations are a major cause of hypermutant cancers, yet questions remain regarding mechanisms of tumorigenesis, genotype–phenotype correlation, and therapeutic considerations. In this study, we establish mouse models harboring cancer-associated POLE mutations P286R and S459F, which cause rapid albeit distinct time to cancer initiation in vivo, independent of their exonuclease activity. Mouse and human correlates enabled novel stratification of POLE mutations into three groups based on clinical phenotype a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…High mutation rates lead to catastrophic accumulation of mutations and cell death [24,28,128]. Consistently, the hypermutator alleles encoding for the analog of P286R change in homozygous state are inviable in mice, while causing cancer when heterozygous [122,135] (Table 2, two last columns of row 3). In the critique of this explanation, we can note that different mutations causing defects of proofreading exo cause different increases of mutation rates (Table 2), and thus it is not clear why tumors do not accumulate "mild" or "leaky" alleles, moderately affecting the exo function of pol δ.…”
Section: Dna Polymerase Genes Mutations In Cancermentioning
confidence: 78%
See 1 more Smart Citation
“…High mutation rates lead to catastrophic accumulation of mutations and cell death [24,28,128]. Consistently, the hypermutator alleles encoding for the analog of P286R change in homozygous state are inviable in mice, while causing cancer when heterozygous [122,135] (Table 2, two last columns of row 3). In the critique of this explanation, we can note that different mutations causing defects of proofreading exo cause different increases of mutation rates (Table 2), and thus it is not clear why tumors do not accumulate "mild" or "leaky" alleles, moderately affecting the exo function of pol δ.…”
Section: Dna Polymerase Genes Mutations In Cancermentioning
confidence: 78%
“…Defects in MMR for a long time were the only factors in hereditary non-polyposis, endometrial, and other cancers in Lynch syndrome, connecting replication fidelity to cancer [116][117][118][119]. The topic of MMR role in cancer is extensively discussed and reviewed [116,[120][121][122] and is not touched here. Recent studies of cancer genomes discovered mutations in genes of the DNA pols of the B family in many sporadic and hereditary cancers [1,2] (Figure 1).…”
Section: Dna Polymerase Genes Mutations In Cancermentioning
confidence: 99%
“…All POLE mutation signatures (SBS 10a, 28 and 10b) were also present in tumors from Pole +/P286R ;Trp53 +/mice (Fig. 3C) 3 , as (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Loss Of P53 Loss Has Minimal Impact On Pole-mediated Tumor Mutation Accumulationmentioning
confidence: 94%
“…We have also shown that p53 is activated in human cancer cell lines engineered to express cancer mutant alleles of POLE 9 . We previously characterized the effects of the Pole-P286R mutation on tumor development and mutagenesis in a mouse model 3 . We noted that Pole P286R/P286R was likely embryonic lethal due to lack of any observed viable offspring.…”
Section: Loss Of P53 Does Not Suppress Pole P286r/p286r Embryonic Lethalitymentioning
confidence: 99%
See 1 more Smart Citation